Attitudes and preferences of non-wooden homeowners in Bachok, Kelantan towards timber as a building material - Eddy Warman, Ruziatul Adibah (2018)
Consumers will need housing units as population that is growing. The demand for wooden houses has decreased because timber is expensive, low durable and hard to obtain. However, there has been no study or data to verify this perception. This study examined the preferences of non-wooden homeowners towards timber as a building material, as well as to examine the preferences of non-wooden homeowners towards timber as a building material. A home-to-home survey was used to collect data from 290 non-wooden homeowners in Bachok, Kelantan. This results show that the homeowners have positive attitudes towards timber in regards to its naturalness, eco-friendly, sustainable, low maintenance, good quality and abundant. The positive attitudes led to preferences toward wooden houses that are unique, comfortable, durable and low maintenance despite the high cost, long construction period and shortage of wooden housebuilding expert. However, most of them prefer non-wooden houses as they are unique, comfortable, durable, low maintenance, low cost, plenty housebuilding expert and short construction period. Timber sector must educate the consumers regarding the actual durability, structural and maintenance of timber.